The hybrid of waqf land and zakat fund development: a case study for protecting asnaf fisabilillah well-being / Siti Nadiah Mohd Ali, Salbiah Mokhtar and Abdul Halim Mohd Noor - Mohd Ali, Siti Nadiah; Mokhtar, Salbiah; Mohd Noor, Abdul Halim (Center for Islamic Philantrophy & Social Finance (CIPSF), 2019)
This research purpose is to explore the hybrid of Waqf land and zakat fund in the development of asnaf fisabilillah needs. Due to the current situation, asnaf fisabilillah in the context of zakat division in modern time interpretation can be used to design socioeconomic development and to uphold the symbolism of Islam. The significant value of understanding this issue will undergo qualitative research based on a paradigm of strategic management theories to suit the internal and the external needs of Pahang SIRC. Using purposive sampling, Pahang SIRC has been chosen to be part of the study where rich data got from the semi-structured interview with three officers. The data were taped, transcribed and analyzed using coding analysis for multiple interviews. Our results inform that, from Pahang SIRC officer’s perspective, there is a need in the hybrid between Waqf land and zakat fund to the well-being of asnaf fisabilillah. The officers are more worried about the benefits of interest they give to the asnaf fisabilillah are insufficient, so that the collection of zakat fund needs to be in the "house." The finding shows that Pahang SIRC has two projects that involved asnaf fisabilillah in the combination of Waqf land and zakat fund. In summary, this study provides some discussion of the single case study which represents a hybrid of Waqf land, and zakat is a comprehensive collaboration within SIRC unit in their operation. The awareness of the knowledge of Waqf land and zakat from the shariah and management principles give a broader perspective to the professionals in Pahang SIRC to contribute to the target group.